Constraint of musculoskeletal tissue and path planning of robot‐assisted fracture reduction with collision avoidance. Issue 2 (8th January 2022) - Xu, Haifei; Lei, Jingtao; Hu, Lei; Zhang, Lihai
Abstract: Background: For the robot‐assisted fracture reduction, due to the complex fracture musculoskeletal environment, it is necessary to consider the influence of soft tissue traction on preoperative reduction path planning. Method: An improved 3D A* algorithm is adopted to plan the fracture reduction path. The distal fragment point clouds are updated to avoid the collision, and the end point coordinates of the muscles are updated to calculate muscular lengths during the path search. Results: 3D reduction path of long‐bone fracture is planned, effectively avoiding the fracture fragments collision and ensuring the length of the corresponding muscle is always less than the allowable maximum muscle length after elongation. Conclusion: The proposed method can effectively avoid the collision between the distal fragment and the proximal fragment during the fracture reduction, can avoid secondary injury of the muscles around the femoral bone caused by over‐distraction, and effectively improve the safety of robot reduction operation.